Thermal Annealing Effect on Optical Properties of the Cadmiun Telluride Films - T.M.В Mazur; V.P.В Makhniy; V.V.В Prokopiv; M.Рњ.В Slyotov (Журнал нано- та електронної фізики)
The thermal treatment effect on optical properties of cadmium telluride thin films was studied. By comparison of the optical transmission spectra and reflection of original and annealed films the formation of modified surfaces was detected. The possibility to get the intense photoluminescence, forming by the band-to-band recombination and transitions as a result of energy dimensional quantization of charge carriers was identified.